Critical Care Nurses Burn Out: Sociodemographic Factors, Leveling and Mitigation in Palestinian Governmental Hospitals - Ahmad Mahmoud Zakarneh, Maram (An Najah National University, 2021)
Aims: Continuous nurses working under stressful situations with critically ill patients decrease their ability to cope with stress, and increase job turnover which expose them to burnout syndrome. So our study aimed to measur the level of critical care nurse’s burnout, verify and find the relationship between sociodemographic risk factors and burnout syndrome, and the effect of break on burnout level among critical care nurses in Palestinian governmental hospitals. Method: Quazi experimental study utilizing a self-report questionnaire, was used to collect data from the critical care nurses in Palestinian governmental hospitals, burnout was measured using Maslach Burnout Inventory- Human Services Survey (MBI-HSS) questionnaire, distributed pretest for both control and intervention groups, intervention was a 20 minutes outdoor break at each shift for 6 weeks, then questionnaire redistributed again posttest for both groups. Result: Result showed total of 110 critical care nurses filled the questionnaire, critical care nurses, of Palestinian governmental hospitals, complained of moderate to high level of emotional exhaustion and depersonalization, while medium to high level of decreased personal achievement. There was a significant difference between burnout and gender and shift rotation also, while there in no significant difference with other sociodemographic factors. There is a significant difference between break and intervention group posttest. Discussion: This study demonstrates that most of the Palestinian critical care nurses complaining of moderate to high level of burnout. Burnout syndrome affected by some sociodemograhic factors such as gender where female had higher level of burnout, and for shift rotation nurses who worked in rotated shifts had higher level of burnout than fixed shifts, and A shift burnout higher than B&C shits, also outdoor break can mitigate level of nurses burnot.
Keywords: sociodemograhic; Quazi; posttest